BELAJAR BERDASAR REGULASI DIRI DALAM PEMBELAJARAN DI PERGURUAN TINGGI - Tekeng, St. Nurjannah Yunus (UIN Alauddin Makassar, 2015)
Abstract: Self-regulated learning is very important for university students to adapt with their academic demand and it is very critical in the lifelong learning process that allow them to face later real life challenges. It refers to their active role in taking responsibility with their learning or their active activities in directing themselves in learning and regulating many areas such as their cognitive, behavior, context, and motivation in order to achieve their learning goals. Self-Regulated learning is based on social cognitive theory and factor affecting it which is explained in the reciprocal triadic between individual, behavior, and environment. Besides, the positive influences of self-regulated learning on students learning have been supported by many empirical evidences.Abstrak: Belajar berdasar regulasi diri sangat penting bagi mahasiswa untuk dapat beradaptasi dengan tuntutan akademik dan sangat penting dalam proses pembelajaran seumur hidup untuk beradaptasi dengan tantangan hidup di masa depan. Belajar berdasar regulasi diri mengacu kepada peran aktif mereka dalam mengambil tanggung jawab dalam belajar atau kegiatan aktif dalam mengaÂrahÂkan diri dalam belajar dengan meregulasi berbagai area seperti kognitif, perilaku, konteks, dan motivasi untuk mencapai tujuan pembelajarannya. Belajar berdasar regulsi diri didasarkan pada teori sosial kognitif dan faktor yang berngaruh dijelaskan dengan hubungan triadik resiprokal antara individu, perilaku, dan lingkungan. Selain itu, pengaruh positif belajar berdasar regulasi diri terhadap pembelajaran telah didukung oleh bukti empiris.